Work Posture and Smoking Habits in Relation to Musculoskeletal Disorders (MSDS) Complaints Among Construction Workers at Dewi Sinta Residence Housing Project, Gunung Kidul Regency - ZulArdi, Subhan; Sari, Retno Purnama (Periodicals of Occupational Safety and Health, 2023)
Inadequate ergonomic conditions at work can lead to the development of muscle and skeletal ailments, such as Musculoskeletal Disorders (MSDs). The construction sector, for instance, is a common setting where these MSDs occur due to non-ergonomic practices. Several factors, including work posture and smoking habits, play a role in influencing the onset of Musculoskeletal Disorders (MSDs). Construction workers may experience MSDs as a consequence of unfavorable work postures that lack ergonomic considerations. The aim of this investigation is to explore the interconnections between work posture, smoking habits, and complaints of Musculoskeletal Disorders (MSDs) among the construction workers at the Dewi Sinta Residence housing project in Gunung Kidul Regency.This study employs a cross-sectional quantitative approach and was conducted at the Dewi Sinta Residence housing project in Gunung Kidul Regency, involving 60 participants. Data collection utilized the Nordic Body Map (NBM) questionnaire and the REBA worksheet. Data analysis involved univariate and bivariate analyses as well as the Chi-Square statistical test. The research findings indicate that work posture (p value = 0.00 < 0.05) and smoking habits (p value = 0.003 < 0.05) are associated with complaints of Musculoskeletal Disorders (MSDs).This study reveals a significant correlation between work posture and smoking habits and the occurrence of Musculoskeletal Disorders (MSDs), they should do short stretching to reduce the pain complained.